The effect of the use of cassava tuber (Manihot esculenta) and Indigofera zollingeriana leaf flour combination as a source of energy supplemented with citric acid in ration on broiler small intestine characteristics and productivity (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: The study aimed to determine the effect of using a combination of cassava tuber (Manihot esculenta) and Indigofera zollingeriana leaf flour as an energy source supplemented with citric acid in the ration on performance, carcass quality, digesta pH, viscosity, and the number of villi in the intestines of broilers. Materials and Methods: The research design was completely randomized with five treatments and five replications, each containing four broilers. The treatment was a substitution of corn in the ration with a combination of cassava tuber and I. zollingeriana leaf (CIF): without CIF, 5% CIF substitute for corn + 0.2% citric acid, 10% CIF substitute for corn + 0.2% citric acid, 15% CIF corn substitute + 0.2% citric acid, and CIF corn substitute + 0.2% citric acid. Each treatment ration was supplemented with 0.2% citric acid. The variables that were looked at were ration consumption, body weight gain, feed conversion, live weight, percentage of the carcass, percentage of abdominal fat, pH, viscosity, and the number of broiler villi. Results: This study showed that the combination of CIF flour supplemented with 0.2% citric acid had a significant effect (p < 0.05) on body weight gain, ration conversion, live weight, carcass percentage, and the number of villi in broiler intestines. But it did not have a significant effect (p > 0.05) on the amount of feed eaten, the amount of fat in the abdomen, the pH of the digesta, or the thickness of the broilers’ blood. Conclusions: The combination of CIF flour at a level of 10% supplemented with 0.2% citric acid can be used as an energy source to replace corn without having a bad effect on production performance, carcass quality, and small intestine characteristics of broilers.  J. Adv. Vet. Anim. Res., 9(3): 471–480, September 2022http://doi.org/10.5455/javar.2022.i616